Design, synthesis and molecular modelling studies of ARYL substituted 2-(4-(Sulfonyl)Styryl) quinazolin-4(3h)-one as potential anticancer agents - Mokganya, Khomotso Jamie (My University, 2024)
In this study, we aimed to synthesize styryl-dihydroquinazolinone derivatives for biological evaluation against cancer. The target compounds were achieved through Iodination of 2- aminobenzamide to yield 5-iodo-2-aminobenzamide 75, followed by a nucleophilic acetyl substitution reaction, to result in 2-aceto-5-iodobenzamide 76. This was then followed by base mediated cyclization reaction of 77 under reflux conditions forming 6-iodo-2-methylquinazolin- (3H)-one 78. A series of substituted-2-hydroxybenzaldehyde derivatives were sulphonated using alkyl and aryl sulfonylchloride derivatives to afford derivatives 79a-r. Amongst them compound 79a, 79b, 79j, 79k were used as substrates for the base mediated Aldol condensation reaction with 6-iodo-2-methylquinazolin-4(3H)-one 78, resulting in the formation of the (E)-4-(2-(6-iodo 4-oxo-3,4-dihydroquinazolin-2-yl)vinyl)-2-sulfonates 80a-d. Application of compounds 80a-d to Suzuki coupling reaction using arylboronic acids under inert conditions afforded novel (E)-4-(2- (6-aryl-4-oxo-3,4-dihydroquinazolin-2-yl)vinyl)-2-sulfonates 81a-e. The synthesized compounds were characterized by a combination of techniques that included nuclear magnetic resonance spectroscopy (1H and 13C NMR), infrared spectroscopy (IR) and mass spectrometry (MS). X-ray analyses were carried out for three sulfonated benzaldehydes 79a, 79b, and 79k. Compound 79a crystalized in a monoclinic crystal system and 79b and 79k in a triclinic crystal system, respectively with space groups P-1 and P21/n respectively. The intermolecular interactions of crystal structures 79a and 79b were further analysed using the Hirshfeld surface analysis. The surface volume and area for 79a (244.26 Å³ and 236.92 Å², respectively) is lower than 79b (322.51 Å³ and 303.35 Å², respectively). A comparison of compound 79a (globularity value of 0.798) relative to 79b (globularity value of 0.750) shows it is higher, meaning it is less spherical. Furthermore, the synthesized compounds were tested for anti-proliferative activity against the breast cancer cells (MCF-7), cervical cancer (HeLa), lung (A549) and human embryonic kidney cells (HEK293-T) using curcumin and camptothecin as a positive control in a MTT cell viability analysis. Compounds 79 a-r were also tested for antioxidative activity using DPPH assay with ascorbic acid as a reference standard. From the preliminary tests, the most active compound, 80c showed 30% cell viability when compared with curcumin 90% cell viability at 100 µM against MCF-7. Compound 80b and 80c and 81e had the most activity against the HeLa cells with a percentage viability of 50%, 51%, and 55% respectively, compared to curcumin at 90%. Compound 80b and 81e resulted in similar %viability of 40% against the HEK293-T cells at 100 µM but the 80b would be most preferred since adhering to ADMET properties. Compounds 79a 79i were also tested for %viability but with camptothecin as a control. Compound 79i was found to be most active with the IC50 value of 0.042 100 µM compared to camptothecin of an IC50 value of 6.32 100 µM. Thereafter compounds 79a-79i were tested for antioxidant activity using the DPPH assay, compounds 79d, 79e, 79f, 79h and 79i have been found to have more scavenging activity (IC50 = 0.29 µM, 0.67 µM, 0.0273 µM and 0.0617 µM) than ascorbic acid (IC50 = 5.87 ± 0.88 µM) and showed strong peroxidase interactions (-7.219 Kcal/mol., -7.087 Kcal/mol., -7.648 Kcal/mol., -7.330 Kcal/mol., and -7.671 Kcal/mol). Perioxidase docking was conducted to elucidate their efficiency of compound 79a-79i, they demonstrated significantly higher binding affinities (ΔG = -5.4 to -8.1 kcal/mol) compared to benzimidazole (ΔG = -5.3 kcal/mol), underscoring their promising potencies. Among these, molecules 79d, 79e, 79h, and 79i displayed particularly strong attachments within the protein binding pockets, interacting with hydrophobic residues such as VAL 916, LEU 889, and VAL 899, akin to the binding pattern observed with benzimidazole. The most active inhibitors of peroxidase were found to be compounds 79h and 79i. Compound 79h formed strong O---H interactions with both hydrophilic xix (ARG 48, PRO 145, HIS 175, LYS 179, THR 234, TYR 187) and hydrophobic (PHE 147) residues, while compound 79i interacted with hydrophilic residues (ARG 48, PRO 145, LYS 179) and one π-π interaction with hydrophobic residue (PHE 191). Compounds 79d and 79e showed the same inhibitory activity, but also differed in their binding energies of -7.087 Kcal/mol. and -7.219 Kcal/mol
Thesis (M.Sc.(Chemistry)) -- University of Limpopo, 2024
Keywords: Cancer; Hydrophilic; Styryl-dihydroquinazolinone; Cells; Human embryonic; Cancer; Cancer -- Molecular diagnosis; Cancer -- Molecular diagnosis; Antineoplastic agents